La motivación a la práctica del baloncesto y el rendimiento deportivo, de los integrantes categoría sub 15 de Liga Deportiva Cantonal de Macará - Garcia Castillo, Juan Carlos (2016)
This research work entitled: MOTIVATION TO PRACTICE BASKETBALL AND ATHLETIC PERFORMANCE, THE MEMBER CATEGORY SUB 15 CANTONAL SPORTS LEAGUE MACARA, whose aim is addressed to: Determine whether the motivation given to athletes team basketball, improves athletic performance in youth sports league cantonal Mascara. How specific objectives: Justify theoretically all about the motivation to sport basketball and athletic performance, diagnose what causes discourage athletes for poor performance in basketball practice, develop, implement and evaluate a program of activities that encourages young people to improve athletic performance in basketball practice. The research is quanta - qualitative. The type of study was longitudinal and pre-experimental design. In research for the purpose of this thesis we have used some research methods such as scientific methods, deduction, -synthesis analysis, historical sense, empirical observation and survey methods, theoretical, probabilistic, mathematical methods, content analysis, cyber, the Empirical evidence is based on field work supported by different instruments including the survey that allowed us to collect data, was also carried out, the application of an initial test and a final test at the same percentage of students, the same as allowed us to confirm the benefits of the proposal, the main results came in this research indicate that there are motivational factors that adversely affect athletic performance of athletes. These results oriented to the realization and implementation of applied proposal: methodological exercise program, to encourage and raise achievement in the discipline of basketball, which had a significant impact on athletes that institution. In conclusion we can say thatthisresearchworksframedinmotivation toperformand the effectit will have onbasketballathletesLigaDeportivaCantonalMacara.